2013
DOI: 10.5941/myco.2013.41.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidaemic Effect ofHericium erinaceumGrown inArtemisia capillarison Obese Rats

Abstract: In this study, ethanolic extracts from Hericium erinaceum cultivated with Artemisia capillaris (HEAC) were assessed for their ability to lower the cholesterol levels of male Sprague-Dawley rats fed a high-fat diet. Rats were randomly subdivided into seven test groups. Each group contained eight rats fed a high-fat diet during a growth period lasting 4 wk. Supplementation with the extracts was performed once a day for 2 wk after the high-fat diet. The control group (rats fed a high-fat diet) showed a high effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…300mg AEHE, when given orally for 7 days, nonsignificant hypolipidemic effects are seen, whereas in the Pre-MCAO HE group significant decline in TC levels in comparison with the MCAO group was seen, which is consistent with the study of Liang et al, who reported a significant decline in plasma TC levels in streptozotocin induced-diabetic model of Wistar rats fed with AEHE 23 . In our study, HDL levels remained normal in the HE-treated, Pre, and Post-MCAO HE groups, consistent with the results of a study conducted on a hyperlipidemia model of rats given ethanol extract of HE a rise in HDL-C levels 24 .…”
Section: Discussionsupporting
confidence: 92%
“…300mg AEHE, when given orally for 7 days, nonsignificant hypolipidemic effects are seen, whereas in the Pre-MCAO HE group significant decline in TC levels in comparison with the MCAO group was seen, which is consistent with the study of Liang et al, who reported a significant decline in plasma TC levels in streptozotocin induced-diabetic model of Wistar rats fed with AEHE 23 . In our study, HDL levels remained normal in the HE-treated, Pre, and Post-MCAO HE groups, consistent with the results of a study conducted on a hyperlipidemia model of rats given ethanol extract of HE a rise in HDL-C levels 24 .…”
Section: Discussionsupporting
confidence: 92%
“…Simvastatin treatment effectively prevented the above pathological changes. This supports recent reports on simvastatin-induced liver histology preservation in high fat diet fed rats 36,47 . Similar preventive effect was observed with all treatments in this study.…”
Section: Effect Of Treatment On Histology Of Heart and Liversupporting
confidence: 93%
“…In the present study, a more favorable reduction of glucose levels was observed with fRG compared to an equal dose of RG. On the other hand, the efficacy of hypolipidemic agents is generally evaluated based on the decrease of serum LDL, triglyceride and total cholesterol with increased HDL levels [ 33 , 34 ]. In the present results, HFD-induced hyperlipidemia was markedly inhibited by treatment with fRG 500 and 250 mg/kg, which was confirmed by decreases in serum LDL, total cholesterol and triglyceride and the increase in HDL.…”
Section: Discussionmentioning
confidence: 99%